Diagnostic Implications of NGS-Based Molecular Profiling in Mature B-Cell Lymphomas with Potential Bone Marrow Involvement - Strasser, Bernhard; Mustafa, Sebastian; Seier, Josef; Wimmer, Erich; Tomasits, Josef (Diagnostics (Basel), 2025)
Background: Methods such as cytogenetics and immunocytology/immunohistology provide essential diagnostic insights but may be limited in ambiguous cases of mature B-cell lymphoma. Next-generation sequencing (NGS) has emerged as a potential tool to improve diagnostics. Methods: We validated the analytical performance of a lymphoid customized NGS panel. Clinical validation was conducted in 226 patients with suspected mature B-cell lymphoma with potential bone marrow involvement across multiple clinically relevant scenarios. Results: NGS (1) achieved 100% sensitivity and specificity with high reproducibility (r = 0.995), confirming its analytical performance. (2) It reliably detected WHO-classified markers, including BRAF mutations in all hairy cell leukemia cases, MYD88/CXCR4 mutations in lymphoplasmacytic lymphoma, and absence of BRAF mutations in splenic B-cell lymphoma with prominent nucleoli. (3) In lymphoma exclusion diagnostics, NGS identified mutations in previously undiagnosed cases, including a BCORL1 mutation leading to reclassification as marginal zone lymphoma. (4) Among 105 confirmed lymphomas, 65% harbored mutations, with detection rates highest in HCL and LPL (100%) and CLL (62%), while follicular lymphoma showed no detectable mutations. (5) In cases with non-interpretable cytogenetics, NGS detected pathogenic variants in 61% of patients, compensating for inconclusive findings. (6) In cases with limited morphological assessment, NGS identified relevant mutations in 70%, outperforming cytogenetics (30%; p = 0.0256, OR = 5.44). Conclusions: NGS enhances the diagnostic accuracy of mature B-cell lymphomas by complementing traditional methods, refining WHO-classified subtypes, and improving detection in cases with inconclusive cytogenetics or morphology. NGS may reduce the need for unnecessary bone marrow re-punctures by providing additional information in ambiguous cases.